2007
DOI: 10.1007/s00261-007-9258-5
|View full text |Cite
|
Sign up to set email alerts
|

Triphasic dynamic CT findings of 63 hepatic focal nodular hyperplasia in 46 patients: correlation with size and pathological findings

Abstract: FNHs with different tumor sizes may manifest various dynamic CT findings that are more or less related to the different pathological findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
2
4
0
2
Order By: Relevance
“…[18][19][20] This is important because small FNH lesions are difficult to diagnose on imaging in that they usually do not display the cardinal features of FNH, especially the central scar, which may be absent in 65% to 88% of cases. 10,[30][31][32] In our study, a central scar was identified on microscopy in 60% of cases, not associated with FNH size. Only 33% (n = 5) of FNH lesions simultaneously showed a central scar, ductular proliferation and dystrophic vessels.…”
Section: Pathological Features Gradingsupporting
confidence: 39%
“…[18][19][20] This is important because small FNH lesions are difficult to diagnose on imaging in that they usually do not display the cardinal features of FNH, especially the central scar, which may be absent in 65% to 88% of cases. 10,[30][31][32] In our study, a central scar was identified on microscopy in 60% of cases, not associated with FNH size. Only 33% (n = 5) of FNH lesions simultaneously showed a central scar, ductular proliferation and dystrophic vessels.…”
Section: Pathological Features Gradingsupporting
confidence: 39%
“…A central scar is seen on CT in approximately 50% of the lesions. Large FNHs (>3 cm) are significantly more likely to reveal central scarring, vascular displacement and abnormal vessels around the lesions than smaller lesions [27,38]. A pseudocapsule is seen in 8% of the FNHs [27].…”
Section: Resultsmentioning
confidence: 99%
“…Повышение интенсивности сигнала в артериальную фазу КТ-исследования и, соответственно, гиперваскулярный вид характерны и для ОУГ печени [20]. При этом чувствительность и специфичность КТ-диагностики ОУГ достигают, соответственно, 83 и 92% [21].…”
Section: актуальные вопросы онкологииunclassified